Fetal adrenal cortex development with maternal serum Cortisol profiles in Relation to Estrous Induction, Laparoscopical Insemination in Iraqi goats out breeding season - Alwan, Ali Fadel (The Iraqi Journal of Veterinary Medicine, 2014)
The objectives of this research were to determine the serum cortisol profiles and their temporal interrelationship during progesterone treatment, induced estrous, laproscopical insemination and pregnancy (antepartum) period in goat, with histological fetal adrenal cortex development.Thefirst part of the experiment included studying Hundred and sixty goat fetuses of different Crown Rump Length (CRL) were collected from slaughter house. The adrenal glands in the goat fetus displayed signs of cytological differentiation around the second half of intrauterine life, 20cm/CRL about 90 days old until full term. From histological observation and physical measurements the present study recorded that the adrenal cortex grow faster from 25 cm/CRL(100 days)to term The majority of this growth take place due to hyperplasia in the adrenal cortex, zone fasciculate. This second part of the experiment condeucted on 16 female local goats aged 2-4yers,weight 30-45Kg. Estrus was inducted by application of impregnated sponges content 20 mg fluorogestone Acetate(FGA) for 13 days and an IM injection of 500 IU Pregnant Mare Serum gonadotropin (PMSG) 24hrs before sponges withdrawal Within 24-36 hrs of estrous sings onset, each doe was inseminated laparoscopically with 1ml of fresh diluted semen contain at least 100 million active fresh sperms directly into the uterine body. Maternal blood samples were collected at day 10th of progesterone treatment, 24hrs after laparoscpical insemination and monthly during pregnancy. The results revealed that all does showed signs of estrous (100%) after 24-72 hrs with a mean time of 46.9±4.90 hrs after sponges removal. Estrous length was 37.1 +1.91 hrs. Pregnancy diagnosis was performed by ultrasonography examination at 30th, 60th and 90th days post insemination. Pregnancy was found in 13 does (81.22%), 3 of them had twin kids (23.01%). Serum cortisol levels shows the highest level during the 4th and 5th months of gestation periods compared to that of the others periods of this study with overall average 78.93+2.96 nmol/L, respectively.